FANDOM


$ \sum_{k=1}^\infty\frac{1}{n^2-a}= $

$ \sum_{k=1}^\infty\frac{1}{n^2+a}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{n^2-a}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{n^2+a}= $

$ \sum_{c:odd}\frac{1}{c^2-a}= $

$ \sum_{c:even}\frac{1}{c^2+a}= $

$ \sum_{k=1}^\infty\frac{1}{n^2-\frac{a}{n^2}}= $

$ \sum_{k=1}^\infty\frac{1}{n^2+\frac{a}{n^2}}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{n^2-\frac{a}{n^2}}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{n^2+\frac{a}{n^2}}= $

$ \sum_{c:odd}\frac{1}{c^2-\frac{a}{c^2}}= $

$ \sum_{c:even}\frac{1}{c^2+\frac{a}{c^2}}= $

$ \sum_{k=1}^\infty\frac{1}{n^4-a}= $

$ \sum_{k=1}^\infty\frac{1}{n^4+a}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{n^4-a}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{n^4+a}= $

$ \sum_{c:odd}\frac{1}{c^4-a}= $

$ \sum_{c:even}\frac{1}{c^4+a}= $

$ \sum_{k=1}^\infty\frac{1}{n^6-a}= $

$ \sum_{k=1}^\infty\frac{1}{n^6+a}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{n^6-a}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{n^6+a}= $

$ \sum_{c:odd}\frac{1}{c^6-a}= $

$ \sum_{c:even}\frac{1}{c^6+a}= $

$ \sum_{k=1}^\infty\frac{1}{(n^2-a)^2}= $

$ \sum_{k=1}^\infty\frac{1}{(n^2+a)^2}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^2-a)^2}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^2+a)^2}= $

$ \sum_{c:odd}\frac{1}{(c^2-a)^2}= $

$ \sum_{c:even}\frac{1}{(c^2+a)^2}= $

$ \sum_{k=1}^\infty\frac{1}{\left(n^2-\frac{a}{n^2}\right)^2}= $

$ \sum_{k=1}^\infty\frac{1}{\left(n^2+\frac{a}{n^2}\right)^2}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{\left(n^2-\frac{a}{n^2}\right)^2}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{\left(n^2+\frac{a}{n^2}\right)^2}= $

$ \sum_{c:odd}\frac{1}{(c^2-\frac{a}{(c^2})^2}= $

$ \sum_{c:even}\frac{1}{(c^2+\frac{a}{(c^2})^2}= $

$ \sum_{k=1}^\infty\frac{1}{(n^4-a)^2}= $

$ \sum_{k=1}^\infty\frac{1}{(n^4+a)^2}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^4-a)^2}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^4+a)^2}= $

$ \sum_{c:odd}\frac{1}{(c^4-a)^2}= $

$ \sum_{c:even}\frac{1}{(c^4+a)^2}= $

$ \sum_{k=1}^\infty\frac{1}{(n^6-a)^2}= $

$ \sum_{k=1}^\infty\frac{1}{(n^6+a)^2}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^6-a)^2}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^6+a)^2}= $

$ \sum_{c:odd}\frac{1}{(c^6-a)^2}= $

$ \sum_{c:even}\frac{1}{(c^6+a)^2}= $

$ \sum_{k=1}^\infty\frac{1}{(n^2-a)^3}= $

$ \sum_{k=1}^\infty\frac{1}{(n^2+a)^3}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^2-a)^3}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^2+a)^3}= $

$ \sum_{c:odd}\frac{1}{(c^2-a)^3}= $

$ \sum_{c:even}\frac{1}{(c^2+a)^3}= $

$ \sum_{k=1}^\infty\frac{1}{\left(n^2-\frac{a}{n^2}\right)^3}= $

$ \sum_{k=1}^\infty\frac{1}{\left(n^2+\frac{a}{n^2}\right)^3}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{\left(n^2-\frac{a}{n^2}\right)^3}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{\left(n^2+\frac{a}{n^2}\right)^3}= $

$ \sum_{c:odd}\frac{1}{(c^2-\frac{a}{(c^2})^3}= $

$ \sum_{c:even}\frac{1}{(c^2+\frac{a}{(c^2})^3}= $

$ \sum_{k=1}^\infty\frac{1}{(n^4-a)^3}= $

$ \sum_{k=1}^\infty\frac{1}{(n^4+a)^3}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^4-a)^3}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^4+a)^3}= $

$ \sum_{c:odd}\frac{1}{(c^4-a)^3}= $

$ \sum_{c:even}\frac{1}{(c^4+a)^3}= $

$ \sum_{k=1}^\infty\frac{1}{(n^6-a)^3}= $

$ \sum_{k=1}^\infty\frac{1}{(n^6+a)^3}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^6-a)^3}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^6+a)^3}= $

$ \sum_{c:odd}\frac{1}{(c^6-a)^3}= $

$ \sum_{c:even}\frac{1}{(c^6+a)^3}= $

$ \sum_{k=1}^\infty\frac{1}{(n^2-a)^4}= $

$ \sum_{k=1}^\infty\frac{1}{(n^2+a)^4}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^2-a)^4}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^2+a)^4}= $

$ \sum_{c:odd}\frac{1}{(c^2-a)^4}= $

$ \sum_{c:even}\frac{1}{(c^2+a)^4}= $

$ \sum_{k=1}^\infty\frac{1}{\left(n^2-\frac{a}{n^2}\right)^4}= $

$ \sum_{k=1}^\infty\frac{1}{\left(n^2+\frac{a}{n^2}\right)^4}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{\left(n^2-\frac{a}{n^2}\right)^4}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{\left(n^2+\frac{a}{n^2}\right)^4}= $

$ \sum_{c:odd}\frac{1}{(c^2-\frac{a}{(c^2})^4}= $

$ \sum_{c:even}\frac{1}{(c^2+\frac{a}{(c^2})^4}= $

$ \sum_{k=1}^\infty\frac{1}{(n^4-a)^4}= $

$ \sum_{k=1}^\infty\frac{1}{(n^4+a)^4}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^4-a)^4}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^4+a)^4}= $

$ \sum_{c:odd}\frac{1}{(c^4-a)^4}= $

$ \sum_{c:even}\frac{1}{(c^4+a)^4}= $

$ \sum_{k=1}^\infty\frac{1}{(n^6-a)^4}= $

$ \sum_{k=1}^\infty\frac{1}{(n^6+a)^4}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^6-a)^4}= $

$ \sum_{k=1}^\infty\frac{(-1)^{n+1}}{(n^6+a)^4}= $

$ \sum_{c:odd}\frac{1}{(c^6-a)^4}= $

$ \sum_{c:even}\frac{1}{(c^6+a)^4}= $